Porównanie dwóch strategii dynamicznego zarządzania portfelem papierów wartościowych - Węgrzyn, Tomasz (Comparison of two dynamic strategies of assets allocation, 2006)
In this article two dynamic strategies of assets allocation are presented. The first strategy is constant-mix strategy. In this strategy manager maintains an exposure to equities that is a constant proportion of his wealth. This strategy is dynamic because whenever the relative value of assets change, purchases and sales are required to return to the desired mix. This strategy is especially profitable when there is high volatility in the market, but when prices are changing in the same direction for a long time this strategy is less profitable than buy and hold strategy. The second strategy is constant proportion portfolio insurance (CPPI). In this strategy the whole portfolio is divided into two parts. One part is invested in equities, while the second part is invested in bonds. When prices are rising bigger part of wealth is invested in equities. So under this strategy manager sells equities as their prices are falling and buy equities as their prices are rising. This strategy is especially profitable when prices are changing in the same direction for a long time, but when there is high volatility in the market it makes loss.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1133, s. 548-556